2018
DOI: 10.1007/s11235-018-0476-7
|View full text |Cite
|
Sign up to set email alerts
|

Burst ratio in a single-server queue

Abstract: In contemporary packet networks, the possibility of packet loss is a negative, but inevitable aspect of the network design. One of the most important characteristics of the packet loss process is the burst ratio-a characteristic describing the tendency of losses to occur in long series, one after another. In this paper, we study the burst ratio in the queueing system with the finite buffer for packets. This is motivated by the fact, that most packet losses in wired networks occur due to queueing of packets in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…We have seen also that the burst ratio depends on the system load in a non-monotonic way, and a maximum can be observed in the curve. For an arrival stream of a simple structure, this maximum is close to ρ = 1, what has been already observed in [ 18 ]. However, the more complex structure of the arrival stream, the more this maximum is shifted towards 0 (herein 0.6 in one of the examples).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We have seen also that the burst ratio depends on the system load in a non-monotonic way, and a maximum can be observed in the curve. For an arrival stream of a simple structure, this maximum is close to ρ = 1, what has been already observed in [ 18 ]. However, the more complex structure of the arrival stream, the more this maximum is shifted towards 0 (herein 0.6 in one of the examples).…”
Section: Discussionsupporting
confidence: 82%
“…In such approach, the actual mechanism of losses is not modeled, what may have some deficiencies, [17]. Analytical studies of the burst ratio in a queueing model in which the losses are actually modeled by buffer overflows, can be found in [18][19][20], for different arrival processes. However, each of these processes has a far less rich structure and modeling capabilities than BMAP.…”
Section: Related Workmentioning
confidence: 99%
“…The burst ratio in finite-buffer queueing systems without the dropping function has been studied recently in [31,32]. Among other things, it was shown that the buffering itself is responsible for tendency of losses in networks to cluster in long sequences; in typical queueing scenarios the values of burst ratio were significantly greater than 1.…”
Section: Burst Ratiomentioning
confidence: 99%
“…Among other things, it was shown that the buffering itself is responsible for tendency of losses in networks to cluster in long sequences; in typical queueing scenarios the values of burst ratio were significantly greater than 1. Moreover, in [31] the system with single-arrival stream was considered, while in [32] the system with bursty traffic was modeled by the batch Poisson process. The bursty traffic in [32] resulted in far worse performance in terms of the average length of the sequence of consecutive packet losses.…”
Section: Burst Ratiomentioning
confidence: 99%
“…This phenomenon was confirmed by direct measurements in a lab and in a real network, [ 2 , 3 ]. It was also explained theoretically, by the derivation of the burst ratio for tail-drop queueing models with various arrival stream types [ 20 , 21 , 22 ]. It is equally easy to understand why the dropping function mechanism can decrease the burst ratio.…”
Section: Introductionmentioning
confidence: 99%